Heteropathogenic virulence and phylogeny reveal phased pathogenic metamorphosis in Escherichia coli O2:H6. Issue 3 (10th January 2014) - Bielaszewska, Martina; Schiller, Roswitha; Lammers, Lydia; Bauwens, Andreas; Fruth, Angelika; Middendorf, Barbara; Schmidt, M Alexander; Tarr, Phillip I; Dobrindt, Ulrich; Karch, Helge; Mellmann, Alexander
Synopsis: Hybrid E. coli pathogens clinical significance was clearly shown during the deadly 2011 outbreak. STEC O2:H6 was diagnosed intestinal and uropathogenic in patients and is shown here as another heteropathogen that emerged via pathogroup conversion. Shiga toxin‐producing Escherichia coli (STEC) O2:H6 were found to be phylogenetically positioned between intestinal pathogenic and uropathogenic E. coli, possess and express virulence factors of both STEC and uropathogenic E. coli, and cause diarrhea as well as urinary tract infections. Based on their phylogeny, virulence features and pluripotential pathogenicity in intestinal and extraintestinal milieus, STEC O2:H6 are proposed to be 'heteropathogens' that occupy an evolutionary and pathogenic interface between intestinal and extraintestinal pathogenic E. coli, and are the first such hybrid virulent E. coli identified. In contrast to the classic view that pathogens emerge from non‐pathogens via sequential, linear acquisition of virulence genes, STEC O2:H6 are portrayed as possessing heteropathogenic virulence potential. The novel evolutionary concept of phased metamorphosis is compelled by our identification of genomes with dual virulence attributes. Broader surveys combining backbone phylogeny and systematic virulence gene analyses are needed to determine if the pathogen emergence via transition is a generalized process. Abstract: Extraintestinal pathogenic and intestinal pathogenic (diarrheagenic) Escherichia coli differ phylogenetically and by virulence profiles. Classic theory teaches simple linear descent in this species, where non‐pathogens acquire virulence traits and emerge as pathogens. However, diarrheagenic Shiga toxin‐producing E . coli (STEC) O2:H6 not only possess and express virulence factors associated with diarrheagenic and uropathogenic E. coli but also cause diarrhea and urinary tract infections. These organisms are phylogenetically positioned between members of an intestinal pathogenic group (STEC) and extraintestinal pathogenic E. coli . STEC O2:H6 is, therefore, a 'heteropathogen, ' and the first such hybrid virulent E. coli identified. The phylogeny of these E. coli and the repertoire of virulence traits they possess compel consideration of an alternate view of pathogen emergence, whereby one pathogroup of E. coli undergoes phased metamorphosis into another. By understanding the evolutionary mechanisms of bacterial pathogens, rational strategies for counteracting their detrimental effects on humans can be developed. Abstract : Hybrid Escherichia coli pathogens clinical significance was clearly shown during the deadly 2011 outbreak. STEC O2:H6 was diagnosed intestinal and uropathogenic in patients and is shown here as another heteropathogen that emerged via pathogroup conversion.